Critical Analysis of the Inclusive Education Implementation in the Concept of Freedom of the Soul and Zona Proximal Development - Wijiastuti, Asri; Masitoh, Siti; Ainin, Ima Kurrotun; Ardianingsih, Febrita (JPI (Jurnal Pendidikan Inklusi))
AbstractKi Hadjar Dewantara laid the foundation of education in Indonesia through his thoughts related to the nature of children in 1913-1919. On the other hand Lev Vygotsky (1896-1934) stated a theory that children are able to learn with the help of competent people. Both theories illustrate that the implementation of education will provide freedom and happiness for children in learning to learn by understanding children naturally and as they are. Research that has been done using ethnographic design aims to dissect and trace Ki Hadjar Dewantara's thoughts and Vygotsky's theory in the implementation of inclusive education. Data collection is done through documentation studies, guided group discussions, and questionnaires. The results of the analysis of the position of Vygotsky's theory in the implementation of inclusive education in the concept of the Zone of Proximal Development are focused on how children construct knowledge according to their culture and ways. The ZPD concept which focuses on cognitive theory emerged around 1993 which in Indonesia itself had been developed by Ki Hadjar Dewantara in 1913-1919 the emphasis was on teaching according to the nature of the child. Ki Hadjar's philosophy is heavily influenced by Maria Montessori's thoughts which emphasize the value of children's independent activities and the importance of children's growth as individuals. In 1952 Ki Hadjar Dewantara created a "system among" approach that put forward â€œFreedom of the Soulâ€. The system that supports the child's natural nature in order to develop inner and outer life according to his own nature. Knowledge and intelligence are only tools, the fruit is the maturity of the soul that can realize life and livelihood in an orderly, holy, and useful for others. The concepts of â€œFreedom of the Soulâ€ and ZPD, are aligned in the cognitive view and efforts of children in obtaining the concept of knowledge in the implementation of education in the classroom.Â AbstrakKi Hadjar Dewantara meletakkan dasar pendidikan di Indonesia melalui pemikirannya terkait dengan sifat anak-anak pada tahun 1913-1919. Di sisi lain, Lev Vygotsky (1896-1934) menyatakan teori bahwa anak-anak dapat belajar dengan bantuan orang yang kompeten. Kedua teori tersebut menggambarkan bahwa implementasi pendidikan akan memberikan kebebasan dan kebahagiaan bagi anak dalam belajar belajar dengan memahami anak secara alami dan sebagaimana adanya. Penelitian yang telah dilakukan dengan menggunakan desain etnografi bertujuan untuk membedah dan melacak pemikiran Ki Hadjar Dewantara dan teori Vygotsky dalam implementasi pendidikan inklusif. Pengumpulan data dilakukan melalui studi dokumentasi, diskusi kelompok terpimpin, dan kuesioner. Hasil analisis posisi teori Vygotsky dalam penerapan pendidikan inklusif dalam konsep Zona Pengembangan Proksimal difokuskan pada bagaimana anak-anak membangun pengetahuan sesuai dengan budaya dan cara mereka. Konsep ZPD yang berfokus pada teori kognitif muncul sekitar tahun 1993 yang di Indonesia sendiri telah dikembangkan oleh Ki Hadjar Dewantara pada tahun 1913-1919 penekanannya adalah pada pengajaran sesuai dengan sifat anak. Filosofi Ki Hadjar sangat dipengaruhi oleh pemikiran Maria Montessori yang menekankan nilai kegiatan mandiri anak-anak dan pentingnya pertumbuhan anak sebagai individu. Pada tahun 1952 Ki Hadjar Dewantara menciptakan pendekatan "sistem di antara" yang mengedepankan "Kebebasan Jiwa". Sistem yang mendukung sifat alami anak untuk mengembangkan kehidupan dalam dan luar sesuai dengan sifatnya sendiri. Pengetahuan dan kecerdasan hanyalah alat, buah adalah kematangan jiwa yang bisa mewujudkan kehidupan dan mata pencaharian secara tertib, suci, dan bermanfaat bagi orang lain. Konsep "Kebebasan Jiwa" dan ZPD, diselaraskan dalam pandangan kognitif dan upaya anak-anak dalam memperoleh konsep pengetahuan dalam implementasi pendidikan di kelas.Â